MATHEMATICAL MODELING AND CORRUPTION-FREE FIXED-POINT STABILITY OF CORRUPTION DYNAMIC WITH CONTROL STRATEGY - Hanan, Hafizhah Atrya; Putri, Arrival Rince; Muhafzan, Muhafzan (LPPM Universitas Bina Bangsa, 2024)
The given work presents a Susceptible Corrupt Jailed Reformed (SCJR) model on corruption spread with a control strategy: encouragement of punishment (in the form of law enforcement). In this mathematical model, it is assumed that corruption spreads like an infectious disease because corrupt individuals can influence susceptible individuals if they interact frequently. This model also assumes that corruption can occur due to personal desires without influence from other individuals. The study shows that the corruption-free fixed point stability depends on the basic reproduction number. The corruption-free fixed point is asymptotically stable if R0<1. The numerical simulations of the corruption-free fixed point and the difference between the model with and without the control strategy are given to demonstrate the validity of the theoretical analysis using Maple software. software Maple